Kriminalitas dan Pembentukan Identitas Sosial Geng Motor - Mudjiyanto, Bambang; Launa; Lusianawati, Hayu (JAMBURA JURNAL ILMU KOMUNIKASI, 2024)
This study aims to explore a number of empirical data in order to analyze the phenomenon of crime and the process of forming the social identity of motorcycle gangs as socio-psychological and socio-cultural symptoms in the current landscape of youth crime. This type of qualitative research with a constructivist paradigm with a socio-psychological and socio-cultural approach found a number of facts, that the phenomenon of motorcycle gangs—whose members are mostly inhabited by gen z’ (teenagers aged 15-23 years)—has long experienced a shift in orientation/ behavior as a result of the influence of the internal and external environment. This shift has resulted in a number of symbolic constructions where motorcycle gangs are perceived as entities that create chaos, initiate violence, commit crimes, spread antisocial attitudes, and seek sensation. Study findings: there are theoretical difficulties in finding a positive self-concept in the majority of motorcycle gang members whose orientation and behavior (empirically) have been infected by symbols of intolerant and antisocial group identities; and suffer from traumatic symptoms, psychosis, phobias, schizophrenia, bipolar, and obsessive compulsive disorder.